2010
DOI: 10.1016/j.jaci.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and characterization of IL-17A expression in patients with chronic rhinosinusitis and its relationship with eosinophilic inflammation

Abstract: be immunogenic in this age group, with all infants enrolled in the study capable of producing adequate serotype-specific IgG to at least 9 of the 23 serotypes at 12 months of age.Nevertheless, there are several issues concerning the use of 23vPPV in children younger than 2 years that require further clarification. It will be important to monitor the kinetics of the immune response over time, because recent studies and our own data raise the possibility that early administration of full-dose 23vPPV may result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 37 publications
8
78
1
Order By: Relevance
“…16 Another study revealed significantly higher level of IL-17A in CRSwNP than CRSsNP with a higher number of subjects. 17 There was 1 study showing increased IL-17C expression in CRSwNP. 5 No study has yet compared IL-17C levels in CRSwNP and CRSsNP nor their correlation with allergy and asthma.…”
mentioning
confidence: 99%
“…16 Another study revealed significantly higher level of IL-17A in CRSwNP than CRSsNP with a higher number of subjects. 17 There was 1 study showing increased IL-17C expression in CRSwNP. 5 No study has yet compared IL-17C levels in CRSwNP and CRSsNP nor their correlation with allergy and asthma.…”
mentioning
confidence: 99%
“…To determine IL-18 expression, double immunohistochemistry was performed using a previously described method [7]. Briefly, sections were incubated with murine antibodies directed against markers of mast cells, eosinophils, neutrophils, B cells, macrophages, T cells, epithelial cells, vascular endothelial cells and fibroblasts, or against control mouse IgG1 (Dako), together with either rabbit anti-human IL-18 antibody or normal rabbit immunoglobulin fraction (Dako) overnight at 4°C (table 2).…”
Section: Methodsmentioning
confidence: 99%
“…It is currently thought that NP formation affects between 1 and 4% of the population [2]. While the precise etiology and pathophysiology underlying CRS remains poorly understood, it has been proposed that networks of Th1, Th2, Th17, and Treg-associated cytokines might be involved [4,5,6,7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We start with the key advances in upper airway diseases which are summarized in Table I. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] …”
mentioning
confidence: 99%